Pre-BMI and Lipid Profiles in Association with the Metabolic Syndrome in Pregnancy with Advanced Maternal Age. (9th July 2022) - Yang, Xinxin; Jiang, Rui; Yin, Xiuping; Wang, Guangya
Abstract : We aimed to explore the association of BMI in pre-pregnant women with metabolic syndrome in pregnancy in advanced maternal age. A total of 229 maternal women and 536 maternal women participated in this study. Pregnancy women underwent a 75 g-oral glucose tolerance test and maternal lipid profile test between 24 and 28 weeks. Data about biological and sociodemographic characteristics were recorded for each case. The metabolic equivalent (Met) was 9.6% in the maternal age ≥35 group, 5.4% in the age 20–34 group ( P  = 0.027), and 6.7% in all pregnant women. Results also demonstrated that gestational diabetes mellitus (GDM) and MetS were more likely to appear in the maternal age ≥35 years group than the maternal age 20–34 years group (41.5% vs. 30.6%; P  = 0.001, 9.6% vs. 5.4%, P  = 0.027). Risk for preterm delivery and eclampsia were increased with raised MetS (RR 3.434 and RR 1.800); MetS in women aged ≥35 years had the largest area under the curve (AUC) (AUC 0.925, 95% CI 0.885–0.965), and its optimal cutoff point was ≥24.998 kg/m 2, and the optimal cutoff point for total cholesterol (TC) (AUC 0.686, 95% CI 0.571–.802) predicting MetS was ≥4.955 mmol/l. MetS in pregnancy are associated with the occurrence of preterm delivery and eclampsia, and pre-BMI and TC can predict MetS in the maternal age ≥35 group.